2017
DOI: 10.1098/rspb.2016.2598
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial reproduction as an adaptation to steep terrain in African toads

Abstract: How evolutionary novelties evolve is a major question in evolutionary biology. It is widely accepted that changes in environmental conditions shift the position of selective optima, and advancements in phylogenetic comparative approaches allow the rigorous testing of such correlated transitions. A longstanding question in vertebrate biology has been the evolution of terrestrial life histories in amphibians and here, by investigating African bufonids, we test whether terrestrial modes of reproduction have evolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…These data suggest that the occurrence of terrestrial species is associated with high humidity in tropical and subtropical areas and is constrained by lower temperatures. Also, an association between terrestrial breeding habits and humid, montane environments has been proposed for a long time (Alcala, 1962;Goin & Goin, 1962) and is supported by local and regional evidence (Jimenez-Robles, Guayasamin, Ron, & Riva, 2017;Liedtke et al, 2017). The mechanism behind this pattern is related to high humidity provided by forest cover and mostly by the scarcity of suitable water bodies in the steep-terrain landscape, where water fails to accumulate in still water bodies and runs as fast-flowing streams (Liedtke et al, 2017;Muller et al, 2013).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…These data suggest that the occurrence of terrestrial species is associated with high humidity in tropical and subtropical areas and is constrained by lower temperatures. Also, an association between terrestrial breeding habits and humid, montane environments has been proposed for a long time (Alcala, 1962;Goin & Goin, 1962) and is supported by local and regional evidence (Jimenez-Robles, Guayasamin, Ron, & Riva, 2017;Liedtke et al, 2017). The mechanism behind this pattern is related to high humidity provided by forest cover and mostly by the scarcity of suitable water bodies in the steep-terrain landscape, where water fails to accumulate in still water bodies and runs as fast-flowing streams (Liedtke et al, 2017;Muller et al, 2013).…”
Section: Introductionmentioning
confidence: 84%
“…World‐wide, amphibian diversity depends greatly on water availability (Buckley & Jetz, ), and we demonstrated that this assumption is valid for both terrestrial and aquatic breeding species. However, although aquatic breeding species depend more on rainfall patterns and availability of aquatic environments (lotic and lentic), the diversity of terrestrial species depends greatly on steeper terrains, which are related to altitude, milder temperatures and higher relative air humidity (Alcala, ; Liedtke et al, ). These differences not only impact amphibian ecology but also have practical consequences for conservation.…”
Section: Discussionmentioning
confidence: 99%
“… Van Bocxlaer et al (2010) first confirmed the long-suspected close phylogenetic relationship between the species recognized by Frost et al (2006) as Mertensophryne and Poyntonophrynus . This result was expanded upon recently by Liedtke et al (2017) who included new data for seven of the ten species included by Frost et al (2006) in Poyntonophrynus .…”
Section: Introductionmentioning
confidence: 88%
“…Sequence assembly was performed using BioEdit 7.0.5.3 ( Hall 1999 ), and new sequences were deposited in GenBank (Table 1 ). The new sequences were then integrated into a data set consisting of all Poyntonophrynus , Mertensophryne , and Capensibufo sequences used in Liedtke et al (2017) , which include 16S and RAG-1, but also sequences of 12S, CO1, ND2, and CXCR4 (Table 1 ). All previously sequenced species of Poyntonophrynus and Mertensophryne were included in that particular data set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation